Identification of CD8+ T cell PRDM1 in high-risk human plaques and its regulatory role in murine lesion development. (10th June 2022) - Maas, SL; Jin, H; Lu, C; Nagenborg, J; Manca, M; Karel, JMH; Cavill, R; Waring, O; Sikkink, CJJM; Mees, BME; Daemen, MJAP; Smirnov, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fritz Thyssen Stiftung T cells have a prominent role in the pathogenesis of atherosclerosis, although their function in atherosclerotic plaques is only partly understood. In this study, we utilize the advantages of high-throughput techniques and data analytic strategies to compare the inherent biological changes of T cells during plaque transition from a stable, non-haemorrhaged (low-risk) to a rupture-prone, haemorrhaged (high-risk) phenotype. We classified 43 human carotid arterial lesions into high- and low-risk plaques based on the presence/absence of intraplaque hemorrhages. RNA from these lesions was isolated and microarray gene expression data was obtained and analyzed by Weighted Gene Co-expression Network Analysis. A strong T cell signalling signature was identified in high- versus low-risk plaques, influencing angiogenesis and interferon-related processes. Bayesian network inference, cell type deconvolution and single-cell RNA sequencing analysis revealed that the T cell-associated gene program was linked to effector-memory cytotoxic, CD8+ T cells. This gene program appeared driven by CD8+ T cell-related transcription factors, including RUNX3, IRF7 and most importantly PRDM1. To validate these findings, we demonstrated in a murine model that T cell PRDM1 plays a key role in plaque formation, as atherosclerotic mice with a T cell specific Prdm1 deficiency developed larger and more advanced atherosclerotic plaques compared to control mice. In conclusion, our study unveils a clear PRDM1-regulated effector-memory cytotoxic CD8+ T cell footprint in plaque development and the shift from low- to high-risk plaques, thereby revealing CD8+ T cells and PRMD1 as potential targets for intervention in adverse T cell responses in human atherosclerotic lesions.